Rheological quality of pearl millet porridge as affected by grits size - Yadav, Deep N. (Springer India, 2014)
Study was conducted to optimize pearl millet grits size for the preparation of acceptable porridge with skimmed milk powder (SMP). Pearl millet porridge was prepared with different grits size (1.410, 0.841, 0.595, and 0.420 mm). A positive (r = 0.904) correlation was observed between water absorption index and grits size. Porridge showed shear thinning behavior as, initially shear stress increased with increase in shear rate and later on decreased. Porridge prepared with larger grits (1.410 mm) exhibited higher firmness (38.4 ± 1.27 N) and viscosity (446 ± 3.9 cP), whereas smaller grits (0.420 mm) resulted in less viscous (118.8 ± 1.74 cP) and firm (20.4 ± 1.85 N) porridge. The medium grits (0.841 mm) produced porridge with acceptable firmness (30.7 ± 1.56 N) and viscosity (298.1 ± 8.81 cP) with moderate (6.0 ± 0.10) acceptability. To improve sensory quality of porridge (grits size 0.841 mm); skimmed milk powder at different levels (0, 5, 10 and 15 %) was added and its effect on various quality parameters was studied. SMP addition significantly (P ≤ 0.05) modified the gelatinization and gelling behavior of grits and decreased (P ≤ 0.05) all the pasting characteristics except pasting temperature, which increased from 77.1 ± 1.85 to 85.9 ± 3.46 °C. The peak (499 ± 6.6 cP) and final viscosity (450 ± 11.9 cP) of porridge (0.841 mm) prepared with 15 % SMP are quite similar. Hence, it maintains viscosity on cooling, similar to maximum viscosity attained during cooking. Keeping in view the rheological, firmness and sensory quality, 0.841 mm grits of pearl millet with 15 % SMP was found optimum for preparation of acceptable porridge.